Comparative study of photovoltaic based power converter topologies for pumping applications - Arun Shankar V.K.; Umashankar S.; Padmanaban S.; Bhaskar M.S.; Ramachandaramurthy V.K.; Fedk V. (Institute of Electrical and Electronics Engineers Inc., 2023)
Centrifugal pumps; Energy conversion; Induction motors; MATLAB; Photovoltaic cells; MATLAB/Simulink environment; Photovoltaic; Power converter topology; Pumping applications; SEPIC; Three phase induction motor; Voltage source inverter; Zeta; Electric inverters